Psychosocial work characteristics, burnout, psychological morbidity symptoms and early retirement intentions: a cross-sectional study of NHS consultants in the United Kingdom - Khan, Atir; Teoh, Kevin; Islam, Saiful; Hassard, Juliet (BMJ Publishing Group Ltd, 2018)
OBJECTIVES: The objectives of this study are twofold. First, to examine the direct effect of psychosocial work characteristics (as measured by job autonomy and work-related pressure) in relation to self-reported psychological morbidity symptoms and early retirement retentions among a sample of hospital consultants in the National Health Service (NHS). Second, to investigate burnout as mediating variable (i.e., indirect effect) of these postulated associations. DESIGN and SETTING: A cross-sectional observational study. PARTICIPANTS: 593 NHS consultants (Male = 63.1%) from hospitals in England, Scotland and Wales. MEASURES Self-reported online questionnaires on work-related pressure and job autonomy (Job Demands-Resources Questionnaire); emotional exhaustion and depersonalisation (Maslach Burnout Inventory); depressive and anxiety symptoms (State Trait Personality Inventory); and a single-item on early retirement intention. RESULTS: Multiple linear regressions examined direct effects, with indirect effects examined using Hayes'1 PROCESS macro. Job autonomy negatively predicted the frequency of NHS consultants’ anxiety and depressive symptoms, and their intention to retire early. No direct relationships involving work-related pressure were observed. Both emotional exhaustion and depersonalisation mediated the relationships that work-related pressure and job autonomy had with symptoms of psychological morbidities. Only emotional exhaustion mediated the relationships where early retirement intention was the outcome. Results of this study observed high prevalence rates across all adverse health measures within this sample, namely: emotional exhaustion (38.7%), depersonalisation (13%), anxiety symptoms (43.1%), and depressive symptoms (36.1%). CONCLUSIONS: This is the first study to observe job autonomy to associate with the number of psychological morbidity symptoms and early retirement intention in a sample of NHS consultants. Burnout dimensions mediated these relationships, indicating that interventions need to focus on enhancing working conditions and addressing burnout among NHS consultants before more severe symptoms of psychological morbidity are reported. This study has implications for NHS policy makers and senior leadership.